Feasibility and efficacy of remotely supervised cranial electrical stimulation for pain in older adults with knee osteoarthritis: A randomized controlled pilot study. (July 2020) - Ahn, Hyochol; Galle, Kelli; Mathis, Kenneth B.; Miao, Hongyu; Montero-Hernandez, Samuel; Jackson, Natalie; Ju, Hsiao-Hui; McCrackin, Heather; Goodwin, Catherine; Hargraves, Allison; Jain, Bhawna; Dinh, Helen; et al.
Highlights: Remotely-supervised cranial electrical stimulation reduced clinical pain. Remotely-supervised cranial electrical stimulation was feasible. Remotely-supervised cranial electrical stimulation was well tolerated. Abstract: Cranial electrical stimulation (CES) is a noninvasive brain stimulation technique that has been shown to improve pain. However, few studies have investigated the potential benefits associated with remotely supervised CES in older adults with knee osteoarthritis (OA). The aim of this study was to examine the feasibility and preliminary efficacy of remotely supervised CES via secure videoconferencing software on clinical pain severity, experimental pain sensitivity, and pain-related cortical response in older adults with knee OA. Thirty participants with symptomatic knee OA pain were randomly assigned to receive 10 daily sessions (60 min each) of remotely supervised CES (n = 15) or sham CES (n = 15) over two weeks. We measured clinical pain severity via a Numeric Rating Scale, experimental pain sensitivity (e.g., heat pain sensitivity, pressure pain sensitivity, and conditioned pain modulation) using quantitative sensory testing, and pain-related cortical response via functional near-infrared spectroscopy imaging. We also measured participant satisfaction with treatment using the Client Satisfaction Questionnaire. Active CES significantly reduced scores on the Numeric Rating Scale and increased heat pain threshold, pressure pain thresholds, and conditioned pain modulation. We also found significant changes in pain-related cortical hemodynamic activity after CES. Participants tolerated CES well without serious adverse effects and were satisfied with the treatment. Our findings demonstrate promising clinical efficacy of remotely supervised CES for older adults with knee OA.